EVALUATION THE PERFORMANCE AND STABILITY OF COWPEA SELECTED GENERATIONS UNDER DROUGHT TOLERANCE - & Abed, Al-Temimi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was conducted at research station of College of Agriculture University of Baghdad in Abu-Griab. The aim was to study early generation of cowpea under water stress regime. The purpose was to diagnose which genotypes have high yield and stability under water deficit. The experiment consisted of two levels of water deficit (50 and 75%) and three genotypes selected and original genotype. Randomized complete block design (RCBD) within split plots arrangement with three replicates in two seasons of 2014 were used. The results revealed that S5 gave highest mean in chlorophyll index and dry matter per induvial plant were 74.66 , 68.44 SPAD. in spring and autumn season respectively. In addition to , S5 had a short period to reproductive phase. S5 gave highest mean seed yield per hectare and water use efficiency were 1246.23 and 2211.84 Kg.ha-1 , 0.19 and 0.51 in spring and autuman seasons, respectively. S4 gave less days to 50% flower were 56.17 and 40.33 in spring and autumn season, respectively. PCV and GCV were so dose in peroxide (13.0 ,12.13%) and (5.70 , 4.68%) in spring and autumn seasons, respectively. Stability values were high in peroxidase , proline , water use efficiency and seed yield (87, 94.3%),( 99.87 , 99.82%), (93.22, 92.33%), (86.5,93.46%) in spring and autumn , respectively. It can be concluded the significant dependance on certain triats in diagnosing the genotypes that tolerated to drought . Therefore S5 was tolerant of drought because of superiority in relative water content. . It is important to use S5 in genotypic and environmental interactions for many years and locations to determine its stability. It can be rationled much quentity of water by following irrigation at 75% . Water deficit which reduced number of irrigation to ten in autumn season, leading to increase of water use efficienly to 0.37 .